Pengaruh Online Visual Merchandising Dan Promosi Penjualan Online Terhadap Impulse Buying Di Aplikasi Tokopedia - Triani, Agnes Bunga; Suryani, Wan (Universitas Medan Area, 2025)
The purpose of this study is to determine what factors trigger potential consumers to buy goods on the marketplace. In addition, to provide additional insight to readers that impulse buying cannot help someone achieve their desired financial goals. The population in this study was 272 people from the Pondok Cindur community. The sample in the study was 73 people taken using the Slovin formula. The data collection technique used in this research was carried out by distributing questionnaires. The analysis techniques used in this research are multiple linear regression, partial test (t test), simultaneous significance test (F test) and coefficient of determination. The research results show that online visual merchandising has a positive and significant effect on impulse buying, sales promotion has a positive and significant effect on impulse buying and online visual merchandising and sales promotion together have a simultaneous effect on impulse buying in the Tokopedia application in the Pondok Cindur community